PENGARUH DISIPLIN TERHADAP PRESTASI KERJA KARYAWAN (Kasus Bagian Finance Khusus Perpajakan PT Chevron Pacific Indonesia Rumbai – Pekanbaru) - Silalahi, Friska Rismauli; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted in PT. Chevron Pacific Indonesia tassel pekanbaru (finance part special case of taxation). The purpose of this study to determine whether the work discipline effect on employee performance. The benefits of research to increase knowladge and insight about the author of the work discipline, especially its influence on employee performance PT. Chevron Pacific Indonesia tassel Pekanbaru.The data analysis technique used is quantitative analysis, statistical test is a simple linear regression analysis. Where there were 24 respondents or samples using census. Data used in this study is primary data and secondary data obtained through the study documentation and qoesioner the measurement using a likert scale and statistically processed with the program SPSS 16.0 for windows, that the t test and the coefficient determinant (R2).Based on the significant test (t-test) can be seen that the variables are partially positively influence and no significant effect on employee’s performance at PT. Chevron Pacific Indonesia tassel pekanbaru (a special case of part finance taxation). Determinan coefficient (R2) value of 0,732 means that the variable is able to explain the work discipline of employee performance by 73,2% and remaining 26,8% is influenced by other factors beyond the research.Keywords : Discipline and Work Performance